Determinants of maternal healthcare utilisation among pregnant women in Southern Ethiopia: a multi-level analysis - Mekdes Kondale Gurara; Veerle Draulans; Jean-Pierre Van Geertruyden; Yves Jacquemyn (BMC, 2023)
Abstract Background Despite efforts to make maternal health care services available in rural Ethiopia, utilisation status remains low. Therefore, this study aimed to assess maternal health care services' status and determinants in rural Ethiopia. Methods The study used quasi-experimental pre- and post-comparison baseline data. A pretested, semi-structured, interviewer-administered questionnaire was used to collect data. A multilevel, mixed-effects logistic regression was used to identify individual and communal level factors associated with utilisation of antenatal care (ANC), skilled birth attendance (SBA), and postnatal care (PNC). The adjusted odds ratio (AOR) and corresponding 95% confidence intervals (CI) were estimated with a p-value of less than 0.05, indicating statistical significance. Results Seven hundred and twenty-seven pregnant women participated, with a response rate of 99.3%. Four hundred and sixty-one (63.4%) of the women visited ANC services, while 46.5% (CI: 42-50%) of births were attended by SBA, and 33.4% (CI: 30-36%) had received PNC. Women who reported that their pregnancy was planned (aOR = 3.9; 95% CI: 1.8-8.3) and were aware of pregnancy danger signs (aOR = 6.8; 95% CI: 3.8-12) had a higher likelihood of attending ANC services. Among the cluster-level factors, women who lived in lowlands (aOR = 4.1; 95% CI: 1.1-14) and had easy access to transportation (aOR = 1.9; 95% CI: 1.1-3.7) had higher odds of visiting ANC services. Moreover, women who were employed (aOR = 3.1; 95% CI: 1.3-7.3) and attended ANC (aOR = 3.3; 95% CI: 1.8-5.9) were more likely to have SBA at delivery. The likelihood of being attended by SBA during delivery was positively correlated with shorter travel distances (aOR = 2.9; 95% CI: 1.4-5.8) and ease of access to transportation (aOR = 10; 95% CI: 3.6-29) to the closest healthcare facilities. Being a midland resident (aOR = 4.7; 95% CI: 1.7-13) and having SBA during delivery (aOR = 2.1; 95% CI: 1.2-3.50) increased the likelihood of attending PNC service. Conclusions Overall, maternal health service utilisation is low in the study area compared with the recommended standards. Women's educational status, awareness of danger signs, and pregnancy planning from individual-level factors and being a lowland resident, short travel distance to health facilities from the cluster-level factors play a crucial role in utilising maternal health care services. Working on women's empowerment, promotion of contraceptive methods to avoid unintended pregnancy, and improving access to health care services, particularly in highland areas, are recommended to improve maternal health service utilisation.